MIDDLE ENGLISH GENERAL CHARACTERISTICS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
Middle English, spoken approximately between 1150 and 1500, represents a transitional stage in the development of the English language between Old English and Modern English. This period was marked by significant social, political, and cultural changes, including the Norman Conquest, which introduced French and Latin influences into English.